Genotype by Diet Interaction on Body Weight of the Local Chicken and its Crosses with Barred Plymouth Rock - Mmereole, F.U.C.; Udeh, I. (International Journal of Poultry Science, 2009)
In a 2x4 factorial arrangement, the effect of genotype, diet and their interaction on body weight and weight gain of the F1 crosses between the local chicken and Barred Plymouth Rock were investigated. Birds of each genotype were separated into two dietary groups at day old. One group was placed on layer type diets and other on broiler type diet. The body weights and weight gains of the two diet groups were monitored up to 12 weeks of age. The effect of genotype by diet interaction on body weight and weight gain was not significant (p>0.05) throughout the period. Birds on broiler diet regime were significantly (p<0.01) heavier at 8 and 12 weeks of age compared with those on layer type diets. The effect of genotype on bodyweight was significant throughout the 12 week period and significant in weight gain at the periods of 0-4 weeks and 4-8 weeks of age only. During these periods, the F1 reciprocal crossbred groups (G2 and G3) compared favourably with the exotic (G4) in weight gain indicating that the local chicken could be used in crosses with the exotic birds for the production of table birds, which are adapted to the local harsh environmental conditions and which are resistant to most of the endemic diseases.